BINARY OPPOSITIONS IN NOTHING SONG BY BRUNO MAJOR: A SAUSSUREAN APPROACH - Shakila, Raisa Irdina; Annisa Luthfiani; Nawal Nuha Yoman; Inayah Ashilah Siregar; Zikrilla Qolbi Elok (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study looks at the lyrics of Bruno Major’s Nothing using Ferdinand de Saussure’s view. The study uses a text-based approach. The study finds three pairs, in the lyrics – intimacy vs. Distance certainty vs. Uncertainty and simplicity vs. Complexity. The opposite pairs shape the structure of the song. The meaning in the lyrics does not come from words. The meaning in the lyrics comes from the contrasts, between signs. The result matches Saussure’s idea that language works through differences. I think the study looks at a gap, in research that rarely uses a Saussurean structural analysis, on a single song. I think the study adds to the growth of using structuralism in the study of music texts. Researchers have examined music texts often with a semiotic approach. In practical terms, the findings of this study can serve as a reference for future studies that seek to examine the meaning of lyrics through oppositional structures, while also emphasizing that songs can be understood as complex sign systems, rather than merely emotional expressions. Overall, this research demonstrates that Nothing conveys emotional depth not through explicit narrative but through subtle oppositional tensions, affirming the relevance of binary oppositions as a tool for understanding meaning in contemporary song lyrics. Keywords: Binary oppositions, song lyrics analysis, meaning.